2017
DOI: 10.1002/mus.25720
|View full text |Cite
|
Sign up to set email alerts
|

The utility of a single simple question in the evaluation of patients with myasthenia gravis

Abstract: The question, "What percentage of normal do you feel regarding your MG?" is feasible and valid, and can be incorporated easily into routine clinical evaluation. Muscle Nerve 57: 240-244, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…The single simple question (SSQ) is a simple and validated question asking what percentage of normal patients feel with respect to their overall MG status, where 0% is worst status and 100% being normal. A recent retrospective study on the utility of the SSQ in MG status showed positive associations with MG scales [3]. Patient acceptable symptom states (PASS) are a way to determine thresholds in outcome measures, where patients feel well overall.…”
Section: Introductionmentioning
confidence: 99%
“…The single simple question (SSQ) is a simple and validated question asking what percentage of normal patients feel with respect to their overall MG status, where 0% is worst status and 100% being normal. A recent retrospective study on the utility of the SSQ in MG status showed positive associations with MG scales [3]. Patient acceptable symptom states (PASS) are a way to determine thresholds in outcome measures, where patients feel well overall.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, we found that Myasthenia Gravis Activities of Daily Living (MG-ADL) had a lower sensitivity for changes in generalized weakness [ 5 ]. In addition, a prior study reported that patients considered limb weakness as most the disabling symptom, further stressing the importance of a high sensitivity for generalized weakness [ 6 ]. The recently developed Myasthenia Gravis Impairment Index (MGII) is a promising measure as it has less floor effects and a higher relative efficiency in its responsiveness to treatment effect compared to other MG measures [ 7, 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, as there is significant phenotypic similarity between various types of polyneuropathy, study results are most likely applicable also for diabetic and other types of polyneuropathy. In addition, we have not explored the responsiveness of the question, in order to determine its role for monitoring changes over time in polyneuropathy severity, although changes in “percentage of normal” did show strong correlation with change in the quantitative myasthenia gravis score . In addition, although patients were asked to address specifically the “percentage of normal” regarding their disease, other comorbidities may affect a patient's sense of well‐being and, consequently, the study question.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have not explored the responsiveness of the question, in order to determine its role for monitoring changes over time in polyneuropathy severity, although changes in "percentage of normal" did show strong correlation with change in the quantitative myasthenia gravis score. 2 In addition, although patients were asked to address specifically the "percentage of normal" regarding their disease, other comorbidities may affect a patient's sense of well-being and, consequently, the study question. In our study we did not systematically collect data regarding all potential comorbidities and their severity, and therefore we did not perform adjustment for comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation